Prevention of firearm-related injuries with restrictive licensing and concealed carry laws: An Eastern Association for the Surgery of Trauma systematic review. Issue 5 (November 2016) - Crandall, Marie; Eastman, Alexander; Violano, Pina; Greene, Wendy; Allen, Steven; Block, Ernest; Christmas, Ashley Britton; Dennis, Andrew; Duncan, Thomas; Foster, Shannon; Goldberg, Stephanie; Hirsh, Michael; et al.
Abstract : BACKGROUND: In the past decade, more than 300, 000 people in the United States have died from firearm injuries. Our goal was to assess the effectiveness of two particular prevention strategies, restrictive licensing of firearms and concealed carry laws, on firearm-related injuries in the US Restrictive Licensing was defined to include denials of ownership for various offenses, such as performing background checks for domestic violence and felony convictions. Concealed carry laws allow licensed individuals to carry concealed weapons. METHODS: A comprehensive review of the literature was performed. We used Grading of Recommendations Assessment, Development, and Evaluation methodology to assess the breadth and quality of the data specific to our Population, Intervention, Comparator, Outcomes (PICO) questions. RESULTS: A total of 4673 studies were initially identified, then seven more added after two subsequent, additional literature reviews. Of these, 3, 623 remained after removing duplicates; 225 case reports, case series, and reviews were excluded, and 3, 379 studies were removed because they did not focus on prevention or did not address our comparators of interest. This left a total of 14 studies which merited inclusion for PICO 1 and 13 studies which merited inclusion for PICO 2. CONCLUSION: PICO 1: We recommend the use of restrictive licensing to reduce firearm-related injuries. PICO 2: We recommend against the use of concealed carry laws to reduce firearm-related injuries. This committee found an association between more restrictive licensing and lower firearm injury rates. All 14 studies were population-based, longitudinal, used modeling to control for covariates, and 11 of the 14 were multi-state. Twelve of the studies reported reductions in firearm injuries, from 7% to 40%. We found no consistent effect of concealed carry laws. Of note, the varied quality of the available data demonstrates a significant information gap, and this committee recommends that we as a society foster a nurturing and encouraging environment that can strengthen future evidence based guidelines. LEVEL OF EVIDENCE: Systematic review, level III.